PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN, INSENTIF DAN DESENTRALISASI TERHADAP KINERJA PEGAWAI BIDANG KEUANGAN SATUAN KERJA PERANGKAT DAERAH (Studi pada Pemerintahan Daerah Kota Pekanbaru) - Tri Suci Dayanti; Raja Adri Satriawan; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to identify and analyze the effect of budget participation, budget goal clarity, incentives and decentralization on the performance of the financial sector employees work unit area of Pekanbaru. The population to be used in this research is that there are local government officials in the regional work units (SKPD) Pekanbaru. Determination of the sample in this study using purposive sampling method for the election that meets the desired criteria researchers. The sample in this study is a government employee who was in the finance department which consists of a head of the division / Head of finance, treasurer and finance department staff totaling 74 people. Analysis of the data used is multiple regression (multiple regression) assisted with SPSS Windows Ver 17. The results of this study prove that budget participation did not affect the performance of employees in finance SKPD Regional Government Pekanbaru. While the budget goal clarity, incentives and decentralization significant effect on the performance of employees in finance SKPD Regional Government Pekanbaru.Keywords: Participation Budgeting, Clarity Budget Targets, Incentives, Decentralization, Performance.